Role of Intrapancreatic SPINK1/Spink3 Expression in the Development of Pancreatitis - Ohmuraya, Masaki; Sugano, Aki; Hirota, Masahiko; Takaoka, Yutaka; Yamamura, Ken-ichi (Frontiers in Physiology, 2012)
Studies on hereditary pancreatitis have provided evidence in favor of central role for trypsin activity in the disease. Identification of genetic variants of trypsinogen linked the protease to the onset of pancreatitis, and biochemical characterization proposed an enzymatic gain of function as the initiating mechanism. Mutations of serine protease inhibitor Kazal type 1gene (SPINK1) are shown to be associated with hereditary pancreatitis. We previously reported that Spink3 (a mouse homologue gene of human SPINK1) deficient mice showed excessive autophagy, followed by inappropriate trypsinogen activation in the exocrine pancreas. These data indicate that the role of SPINK1/Spink3 is not only trypsin inhibitor, but also negative regulator of autophagy. On the other hand, recent studies showed that high levels of SPINK1 protein detected in a serum or urine were associated with adverse outcome in various cancer types. It has been suggested that expression of SPINK1 and trypsin is balanced in normal tissue, but this balance could be disrupted during tumor progression. Based on the structural similarity between SPINK1 and epidermal growth factor (EGF), we showed that SPINK1 protein binds and activates EGF receptor, thus acting as a growth factor on tumor cell lines. In this review, we summarize the old and new roles of SPINK1/Spink3 in trypsin inhibition, autophagy, and cancer cell growth. These new functions of SPINK1/Spink3 may be related to the development of chronic pancreatitis.